2019
DOI: 10.5194/acp-19-9321-2019
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase separation in secondary organic aerosol particles produced from <i>α</i>-pinene ozonolysis and <i>α</i>-pinene photooxidation with/without ammonia

Abstract: Abstract. Recently, liquid–liquid phase separation (LLPS) of secondary organic aerosol (SOA) particles free of inorganic salts has been intensively studied due to the importance of cloud condensation nuclei (CCN) properties. In this study, we investigated LLPS in four different types of SOA particles generated from α-pinene ozonolysis and α-pinene photooxidation in the absence and presence of ammonia (NH3). LLPS was observed in SOA particles produced from α-pinene ozonolysis at ∼95.8 % relative humidity (RH) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 59 publications
4
36
0
Order By: Relevance
“…This is in part due to challenges related to sampling and isolating sufficient amounts of organosulfate material from atmospheric organic aerosol for the subsequent analysis of single component properties, as well as synthesizing adequate amounts of known organosulfate reference compounds. The hygroscopic properties of organosulfate-containing aerosol have been measured using sodium salts of alkane sulfates (Woods III et al, 2007;Estillore et al, 2016) and limonene-derived organosulfates (Hansen et al, 2015). Limonene-derived organosulfate was demonstrated to lower the surface tension of aqueous solutions even more effectively than atmospherically relevant strong organic acids (Hansen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is in part due to challenges related to sampling and isolating sufficient amounts of organosulfate material from atmospheric organic aerosol for the subsequent analysis of single component properties, as well as synthesizing adequate amounts of known organosulfate reference compounds. The hygroscopic properties of organosulfate-containing aerosol have been measured using sodium salts of alkane sulfates (Woods III et al, 2007;Estillore et al, 2016) and limonene-derived organosulfates (Hansen et al, 2015). Limonene-derived organosulfate was demonstrated to lower the surface tension of aqueous solutions even more effectively than atmospherically relevant strong organic acids (Hansen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these recent studies investigated SOA generated from a single VOC (e.g., α-pinene or isoprene). However, in the atmosphere, SOA is formed from a complex mixture of VOCs (Odum et al, 1997;Schauer et al, 2002a, b;Vutukuru et al, 2006;Velasco et al, 2007;de Gouw et al, 2008;Velasco et al, 2009;Liu et al, 2012;Hayes et al, 2015). Additional studies are needed to determine if SOA generated from a complex mixture of VOCs of atmospheric relevance can also undergo LLPS at high RH.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel fuel contains a wide range of VOCs including aromatics and alkanes. Furthermore, SOA generated from the photooxidation of diesel fuel vapors may be a good proxy for SOA from anthropogenic emissions (Odum et al, 1997;Schauer et al, 2002a, b;Vutukuru et al, 2006;Velasco et al, 2007Velasco et al, , 2009de Gouw et al, 2008;Gentner et al, 2012Gentner et al, , 2017Liu et al, 2012;Jathar et al, 2013Jathar et al, , 2014Hayes et al, 2015;Blair et al, 2017;Jathar et al, 2017). In this study, we investigate LLPS and viscosity within SOA particles generated by photooxidation of diesel fuel vapors.…”
Section: Introductionmentioning
confidence: 99%
“…With O:C ratios of the monoterpene and isoprene derived organosulfates in the ranges 0.5-0.7 and 1.2-1.4, respectively, these results are consistent with the present work. On the other hand, in experiments of OH oxidized α-pinene and water system (Ham et al, 2019) only a single organic-rich phase was observed, whereas LLPS was seen between water and ozone oxidized α-pinene products (Ham et al, 2019) or OH oxidized isoprene products (Rastak et al, 2017).…”
Section: Solubility In Aqueous Ammonium Sulfate and Bisulfate Solutionsmentioning
confidence: 90%
“…Liquid-liquid phase separation (LLPS) has been detected in several aerosol experiments (Song et al, 2012;Rastak et al, 2017;Song et al, 2018;Ham et al, 2019). For example, Song et al (2012) observed LLPS for ammonium sulfate aerosol containing organic compounds with O:C below 0.8, whereas no LLPS was seen with O:C above 0.8, depending on the functional groups.…”
Section: Solubility In Aqueous Ammonium Sulfate and Bisulfate Solutionsmentioning
confidence: 99%